Louise loves art - Light, Kelly, 1970- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2014)
A young girl who loves to draw and display her masterpieces at the "gallery du fridge" is too busy to pay attention to her little brother who wants to make a masterpiece of his own.